Tre scienze filosofiche della religione: ambiguità, intreccio e generazione - Yeung, L.C., Alex (Alpha Omega, 2021)
Summary: This article compares the object and method of three philosophical sciences that study God: the phenomenology of religion, the philosophy of religion, and natural theology. Reflecting on how God enters philosophy reveals the presence of a transcendent ambiguity (or irreducible polarity) in each of these three sciences, leaving room for, or even requiring, taking a stand – a call to faith or no-faith – on the part of the researcher. In this sense, none of the three disciplines turns out to be absolutely primary; rather, each is interwoven in distinct ways with the other two, depending on its own perspective. Applying Étienne Gilson’s methodological adage – "faith generative of reason" – the article concludes by suggesting how the particular manner of (Christian) belief ends up favoring one of the three sciences as the basic philosophical science in the study of God. Key words: Phenomenology of religion, philosophy of religion, natural theology, Religious Studies methodology, Christian philosophy, Étienne Gilson, faith and reason. Parole chiave: Fenomenologia della religione, filosofia della religione, teologia naturale, metodologia di Religious studies, filosofia cristiana, Étienne Gilson, fede e ragione.